Thermodynamic properties of ZnTe - Nasar A.; Shamsuddin M. (My University, 2025)
The free energy of formation of ZnTe has been determined by an electrochemical technique. From the open-circuit e.m.f. of the galvanic cell at different temperatures the following ΔG° vs. T relationships have been established ΔG°f = - 119 355 + 12.39T J mol-1 (640 < T < 693 K)ΔG°f = - 126 870 + 23.18T J mol-1 (693 < T < 723 K)ΔG°f = - 145 110 + 48.41T J mol-1 (723 < T < 845 K) The enthalpies of formation and fusion have been measured by differential thermal analysis. The combined investigations yield values of ΔG°f,298K, ΔH°f,298K, ΔS°f,298K, ΔS°298K, ΔHf and ΔSf to be -115.2 ± 1.0 kJ mor-1, -119.0 ± 2.0 kJ mol-1, -12.75 J K-1 mol-1, 78.4 J K-1 mol-1, 63.0 ± 2.5 kJ mol-1 and 40.1 ± 1.6 J k-1 mol-1 respectively. The results are compared with the thermodynamic data available in the literature and discussed in terms of the structure and bonding of the compound. © 1990.